Plasma and CSF pharmacokinetics of meropenem in neonates and young infants: results from the NeoMero studies. (19th April 2018) - Germovsek, Eva; Lutsar, Irja; Kipper, Karin; Karlsson, Mats O; Planche, Tim; Chazallon, Corine; Meyer, Laurence; Trafojer, Ursula M T; Metsvaht, Tuuli; Fournier, Isabelle; Sharland, Mike; Heath, Paul; et al.
Abstract: Background: Sepsis and bacterial meningitis are major causes of mortality and morbidity in neonates and infants. Meropenem, a broad-spectrum antibiotic, is not licensed for use in neonates and infants below 3 months of age and sufficient information on its plasma and CSF disposition and dosing in neonates and infants is lacking. Objectives: To determine plasma and CSF pharmacokinetics of meropenem in neonates and young infants and the link between pharmacokinetics and clinical outcomes in babies with late-onset sepsis (LOS). Methods: Data were collected in two recently conducted studies, i.e. NeoMero-1 (neonatal LOS) and NeoMero-2 (neonatal meningitis). Optimally timed plasma samples ( n = 401) from 167 patients and opportunistic CSF samples ( n = 78) from 56 patients were analysed. Results: A one-compartment model with allometric scaling and fixed maturation gave adequate fit to both plasma and CSF data; the CL and volume (standardized to 70 kg) were 16.7 (95% CI 14.7, 18.9) L/h and 38.6 (95% CI 34.9, 43.4) L, respectively. CSF penetration was low (8%), but rose with increasing CSF protein, with 40% penetration predicted at a protein concentration of 6 g/L. Increased infusion time improved plasma target attainment, but lowered CSF concentrations. For 24 patients with culture-proven Gram-negative LOS, pharmacodynamic target attainment was similar regardless of the test-of-cure visit outcome. Conclusions: Simulations showed that longer infusions increase plasma PTA but decrease CSF PTA. CSF penetration is worsened with long infusions so increasing dose frequency to achieve therapeutic targets should be considered.